Memory Ireland : Volume 2: Diaspora and Memory Practices - Frawley, Oona (Irish studies (Syracuse, N.Y.), 2012)
Irelands status as an island nation with a history of emigration has meant the development of a body of diasporic cultural memory. This book opens new pathways into the body of Irish cultural memory, demonstrating time and again the ways in which memory is supported by the negotiations of individuals within wider cultural contexts.